Más allá de las Naciones Revoluciones, contrarrevoluciones e independencias (1795-1830) - Bereche, Leonardo; Martínez, César; Martínez-Flener, Milagros (Ariadna Ediciones, 2023)
Juan Marchena pointed out at the time, that "you have to stop following looking at our navels". This phrase, intended for the context of independence American, reflects his deep concern for a story that would break the local schemes, national borders and interconnected with a larger than would allow us to analyze the future of America, linking events both Americans as Europeans. Within this framework, he would also place emphasis on the analysis of social dynamics, many of them conditioned by political, social, economic and geographical contexts, among others. One of his references would be the repercussions of the French Revolution in the Caribbean, and its direct influence on the movements in Martinique (1790-1793), Guadeloupe (1795-1802) and the most relevant, Haiti (1804); this The latter, I would point out, would in turn have an effect on those that broke out in Venezuela and, in addition to arousing fears throughout Spanish America due to its political scope, it would also do so because it was a rebellion led by black slaves against the white European elite established in the new World.